Unlocking the Power of Metacognition: The Role of Metacognitive Skills in Decision-Making using Type I/II Thinking - Pavao, Sylvanna (Université d'Ottawa | University of Ottawa, 2026)
Strong reasoning skills are vital in a variety of academic and everyday contexts, requiring strong metacognitive awareness to be strategic and efficient. However, relatively little is known about how metacognitive abilities and skill-building relate to making purposeful choices about reasoning. We investigated the role of metacognition in Dual Process theory, including learners’ awareness and self-description of their cognitive engagement. Dual-process theory describes that most reasoning results from the interaction of two cognitive processes: Type I (fast/intuitive thinking) and Type II (slow/analytical thinking). The purposeful use of reasoning types is complex, including metacognitive awareness of the Type being used, identifying the optimal type, deciding if there is a need or benefit to switching, desire/motivation to switch, and the ability to do so (e.g., cognitive resources). This mixed-methods study examined how a metacognition intervention influenced awareness of and engagement with Type I/II thinking, and the impacts of training in discipline agnostic and discipline specific contexts (organic chemistry). Using an experimental design that included pre- and post-tests, participants completed a worksheet targeting Type I/II reasoning three times over two weeks. Participants in the treatment/intervention group completed a metacognition learning module, while the control group completed an unrelated activity. In the worksheets, participants identified the thinking type they engaged with for questions and explained their thought process. We found that having an organic chemistry background and/or belonging to a particular group (intervention/control) were correlated with differences in analytical engagement. Participants in the treatment group demonstrated more deliberate monitoring and regulation of their reasoning, whereas participants in the control group relied on rigid, superficial distinctions between thinking types. Metacognitive accuracy and regulation varied across groups.
Keywords: Chemistry Education; Metacognition; Cognitive Regulation; Type I/II Thinking